2020
DOI: 10.1007/978-3-030-50896-8_50
|View full text |Cite
|
Sign up to set email alerts
|

VR in Education: Ergonomic Features and Cybersickness

Abstract: This paper describes theory (systemic structural model) of learning activity in the virtual reality, as well as demonstrates (on experimental data) in psychophysiological regulation of the cognitive activity in VR. Understanding of these changes can be used for learning improvement using VR environment regards the interrelationship between the structure and self-regulation of learning activity, avoiding potential cybersickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…Consistent with previous studies, the participants only reported mild general side effects (Cybersickness) which ameliorated quickly after several minutes ( 16 , 47 ). None of the participants reported any psychosis-like symptoms, neither right after the experience, nor after 1 week and 1 month of follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, the participants only reported mild general side effects (Cybersickness) which ameliorated quickly after several minutes ( 16 , 47 ). None of the participants reported any psychosis-like symptoms, neither right after the experience, nor after 1 week and 1 month of follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, the approaches of Pinchuk et al [25] applied to VR design taking into account the recommendations and research results in the field of ergonomics are important.…”
Section: Factors Contributing To the Development Of Cybersicknessmentioning
confidence: 99%
“…Аналіз останніх досліджень і публікацій. Серед вчених дослідників, які займаються сучасними інноваційними технологіями в освіті можна виділити: С. Ахаджанова [2], О. Буров [2], Т. Вакалюк [1], Н. Волик [7], О. Глазунова [2], В. Осадчий [1], В. Коваленко [3], А. Кух [6], М. Мар'єнко [3], І. Пахомова [4]…”
unclassified